Factors Associated with the Utilization of Health Services Among Decompression Patients in the Soropia Health Center Area - Rano, Rano; Munir, Sanihu; Noviyanti Rahcman, Wa Ode Nova (Waluya The International Science of Health Journal, 2026)
Introduction: Health services are essential facilities needed by communities to achieve optimal health. One common health problem experienced by fishermen is decompression sickness. Data from the Soropia Health Center showed that 25 cases of decompression sickness occurred in 2022, 33 cases in 2023, and 44 cases in 2024. This study aimed to analyze the relationship between information sources and health facilities and the utilization of health services among decompression sufferers in the Soropia Health Center working area. Method: This research is quantitative and cross-sectional. It was conducted in August 2024. The population was all 44 fishermen experiencing decompression in Soropia District, and a sample of 44 people was taken using total sampling. Data were collected using a questionnaire and tested using chi-square tests, correlation tests, and binary logistic regression. Result: Based on the Chi-Square test of knowledge (p value 0.011 and closeness ⱷ 0.421), health information (p value 0.001 and closeness ⱷ (0.553), facilities (p value 0.005 and closeness ⱷ 0.553). Conclusion: There is a moderate relationship between information sources and facilities and the use of health services in decompression patients.